NEW ROUTE FOR THE SYNTHESES OF ITS SOME NOVEL DERIVATIVES OF 3-ARYL BENZO[D]THIAZOLE-2(3H)-IMINE FROM HIGH SUBSTITUTED THIOUREAS - Marzieh Miar; Khalil Pourshamsian; Abolfazl Shiroudi; Farhad Hatamjafari; Ahmad Reza Oliaey (Journal of the Chilean Chemical Society, 2020)
We have developed herein a new approach to diverse synthesis of novel derivatives of 3-Aryl benzo[d]thiazole-2(3H)-imines (3a-g), by a two-component reaction between diazonium salt (2) and various synthesized N-acyl-N'-aryl thioureas (1a-g), in the presence of sodium tert butoxide as strong base. Finally, it resulted in the production of the desired product with a moderate yield. The chemical structures of these synthesized compounds were confirmed by various physico-chemical methods viz. FT-IR, 1H-NMR, 13C-NMR and elemental analysis.